1999
DOI: 10.1074/jbc.274.18.12656
|View full text |Cite
|
Sign up to set email alerts
|

The Neuron-specific K-Cl Cotransporter, KCC2

Abstract: The neuron-specific K-Cl cotransporter (KCC2) is hypothesized to function as an active Cl ؊ extrusion pathway important in postsynaptic inhibition mediated by ligand-gated anion channels, like ␥-aminobutyric acid type A (GABA A ) and glycine receptors. To understand better the functional role of KCC2 in the nervous system, we developed polyclonal antibodies to a KCC2 fusion protein and used these antibodies to characterize and localize KCC2 in the rat cerebellum. The antibodies specifically recognized the KCC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…The maintenance of such low levels of intracellular Cl Ϫ ions is responsible for hyperpolarizing Cl Ϫ currents upon activation of GABA A and Gly receptors, which are responsible for fast synaptic inhibition in the adult central nervous system (2)(3)(4)(5). Molecular studies have demonstrated that KCC2 is a member of a CCC superfamily and that these transporters are composed of 12-transmembrane domains with N-and C-terminal cytoplasmic domains (2,6,7). KCC2 is expressed exclusively in neurons throughout the adult brain.…”
mentioning
confidence: 99%
“…The maintenance of such low levels of intracellular Cl Ϫ ions is responsible for hyperpolarizing Cl Ϫ currents upon activation of GABA A and Gly receptors, which are responsible for fast synaptic inhibition in the adult central nervous system (2)(3)(4)(5). Molecular studies have demonstrated that KCC2 is a member of a CCC superfamily and that these transporters are composed of 12-transmembrane domains with N-and C-terminal cytoplasmic domains (2,6,7). KCC2 is expressed exclusively in neurons throughout the adult brain.…”
mentioning
confidence: 99%
“…HEK293 cells, and Xenopus oocytes. In this study, we therefore examined the role and mechanisms of tyrosine phosphorylation in the regulation of KCC2 function in cultured hippocampal neurons and in GT1-7 cells, a brain-derived cell line that possesses many neuronal characteristics but does not express endogenous KCC2 (18,19) (also, see "Experimental Procedures"). The present study proposes that tyrosine phosphorylation of KCC2 results in clustering within lipid rafts via interactions within the carboxyl terminus of KCC2 and that this clustering results in efficient extrusion of Cl Ϫ .…”
mentioning
confidence: 99%
“…Third, KCC2 has perhaps the most clearly defined physiological role of the four KCCs. KCC2 is thus a neuron-specific gene (22,23), with a crucial role in determining intracellular chloride activity ([Cl Ϫ ] i ) and the neuronal response to GABA and glycine (24,25). Early in postnatal life there is robust neuronal expression of the Na ϩ -K ϩ -2Cl Ϫ cotransporter NKCC1 (26), with only minimal expression of KCC2.…”
mentioning
confidence: 99%